Evaluation of Extreme Rainfall Occurrences Using Short-term and Long-term Standard Precipitation Index (SPI) - Razuki, Nurul Dayana; Abdul Rauf, Ummul Fahri; Zainol, Zuraini; Mohd Isa, Mohd Rizal; binti Jamaludin, Nor Azliana Akmal (JOIV : International Journal on Informatics Visualization, 2025)
The main objective of this study is to investigate the Standard Precipitation Index (SPI), a method commonly used to determine extreme rainfall occurrences. It is also used to gauge the severity and duration of drought in meteorological studies. To highlight exceptional extreme rainfall events in selected areas, a methodology for calculating the SPI was provided in this paper using a range period and thresholds. The Standard Precipitation Index (SPI) is used to analyze monthly precipitation data from several selected rain gauge stations between 1970 and 2014. The goal of this study is to monitor the extremely moist conditions that may eventually lead to flooding. Precipitation index data from several rain gauge sites in the selected region are used to calculate the SPI time series. Additionally, SPI readings for 3 months or less may usually be used for basic drought monitoring, values for 6 months or less may be useful for monitoring agricultural impacts, and values for 12 months or more may be useful for monitoring hydrological impacts. In this study, two states affected by the monsoon season were selected: Johor and Kelantan. Two rain gauge stations were selected from these two states to calculate the SPI results. From this study, statistics on the occurrence of dry and wet events in specified areas were determined based on the SPI readings for 3-month, 9-month, 12-month, and 24-month periods. To summarize, this research demonstrates the potential of SPI to enhance our understanding of extreme rainfall events in Peninsular Malaysia.